What is the current state of anxiety and its related factors in Chinese patients undergoing colonoscopy? A cross-sectional study - Qian-Qian Yue; Ge-Hui Feng; Tong Peng; Tian Tang; Ying-Xue Sun; Xin-Ru Meng; Li-Li Huang; Ke-Hao Zhao; Hui-Lin Huang; Ying Zeng (BMC Psychology)
Abstract Background Anxiety in patients undergoing colonoscopy may also result in adverse effects, including altered vital signs such as elevated heart rate and blood pressure, exacerbation of symptoms like bloating and gastrointestinal discomfort, a decline in cooperation and satisfaction, and even colonoscopy failure. However, limited studies have explored the level of anxiety, factors that influence it, and its specific causes. Methods A cross-sectional study was conducted, recruiting 825 patients undergoing colonoscopy in Hunan Province between January and July 2023 using stratified sampling. The Spielberger State-Trait Anxiety Inventory (STAI), a self-designed demographic characteristics questionnaire, and a colonoscopy patient anxiety influencing factor questionnaire were used. The data were analyzed in SPSS (version 26) using Mann–Whitney U, Kruskal–Wallis, and multiple regression analysis tests. Results The final study included 825 participants, of whom 19.8% exhibited mild anxiety, 37.0% exhibited moderate anxiety, and 43.2% exhibited severe anxiety. The results indicated that insomnia (β=-0.080, p = 0.013), no comorbidities (β=-0.147, p < 0.001), not smoking or drinking (β=-0.158, p < 0.001), and poor health (moderate: β=-0.183, p < 0.001; poor: β=-0.164, p < 0.001) were negatively associated with anxiety levels. In contrast, marital status (β = 0.177, p < 0.001), education level (β = 0.204, p < 0.001), age (β = 0.114, p = 0.007), medical insurance (Basic Medical Insurance for Urban Residents β = 0.204, p < 0.001; Commercial medical insurance: β = 0.112, p < 0.001), care provided by relatives (β = 0.102, p = 0.002), diarrhoea (β = 0.089, p = 0.005), occupation (farmers: β = 0.099, p = 0.009; self-employed: β = 0.082, p = 0.014), and paternal upbringing (β = 0.067, p = 0.034) were positively correlated with anxiety. Several factors had a greater impact on the anxiety level of the patients: education level (β = 0.204), health status (moderate: β=-0.183; not good: β=-0.164), and marital status (β = 0.177). It probably because higher education levels may increase awareness of potential risks associated with colonoscopy, contributing to greater anxiety. The five common reasons for anxiety included the presence of bloody faeces, enemas, need for further treatment, lack of timely feedback from the physician, lack of an accurate diagnosis. Conclusion The level of anxiety experienced by patients during the colonoscopy phase was more severe and should be alleviated with targeted interventions based on the cause of anxiety, such as pre-procedural counseling, patient education materials, and enhanced communication with healthcare providers.